Implementasi Kelas Kreatif Berbasis Alam Di Sekolah Dasar Lingkungan Lahan Basah - Siti Fatimah; Ahmad Suriansyah; Arta Mulya Budi Harsono (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
Learning that is still centered on traditional classrooms often makes students less active and minimally involved with the environment. This research aims to analyze the implementation of nature-based creative classes as a strategy to increase learning comfort, motivation, and environmental care character in elementary school students in wetland areas. The research uses a qualitative case study design at SDN SN Sungai Miai 5 Banjarmasin with data collection through interviews, observations, and documentation. The research analysis unit is the teacher's adaptive practice in designing, managing, and growing a nature-based classroom culture. Research results show that the implementation of nature-based creative classes is an integrated strategy with five main themes: the concept of nature-based space, adaptive space arrangement, the impact of nature classes on comfort and learning focus, the role of teachers as designers and facilitators, as well as the formation of student values and characters. This finding confirms that the creativity and pedagogical leadership of teachers is able to produce contextual learning that is in accordance with the characteristics of the wetland ecosystem and can be replicated in schools with similar conditions.